Overview of Nutritional Status and Symptoms of Diabetic Gastroparesis in Patients With Type 2 Diabetes Mellitus with Uncontrolled Blood Glucose Levels - Kirana, Ade; Pahria, Tuti; Nursiswati, Nursiswati (Indonesian Journal of Global Health Research, 2024)
Gastroparesis is a complication experienced by 20% - 50% of chronic diabetes mellitus patients with poor glycemic control. Hyperglycemia will slow down gastric emptying thereby reducing oral intake and mismatch of nutrient absorption which causes impaired nutritional status. Objective: to determine the nutritional status and symptoms of diabetic gastroparesis in type 2 diabetes mellitus patients with uncontrolled blood glucose levels. Method: Quantitative descriptive study on type 2 DM patients at RSAU Dr. M. Salamun. The sampling technique uses consecutive sampling with a sample size of 82 subjects. Data were obtained through gastrointestinal symptom score (GSS) questionnaires, height and weight checks, and patient medical records. Furthermore, the data results will be processed using univariate analysis. The questionnaire is considered reliable with the results of the reliability test of the crombach alpha value >0.50. Result: 71.9% of respondents experienced symptoms of diabetic gastroparesis with normal nutritional status (37.1%) and obesity (37.1%). The majority were female, ≥60 years old, and 1-5 years of DM. Conclusion: Health education and intervention in modifying lifestyle better so that it can control blood glycemia and make a diet that is suitable for patients with gastroparesis so that it can minimise the symptoms of gastroparesis experienced.